Managerial Ability dan Earnings Quality (Studi pada Perussahaan Manufaktur di BEI): Keywords: Managerial Ability; earnings Quality; Earnings persistence; Earning Sustainability; Accruals Quality - Carolyn Lukita (Universitas Negeri Surabaya, 2022)
This study aimed to identify factors that can improve earnings quality. Earnings Quality has been measured by three measurements such as; sustainable earnings, earnings persistence and quality accruals. The results showed that managerial ability had a positive effect on earnings quality, managerial abilities were proven to improve earnings quality. Specifically, managers that have better understanding abaout the company's opportunities and risks so that they can generate persistence profits, have better predictive values ​​and accrual estimates. This study contributes to finding one variable that can significantly affect earnings quality, namely managerial ability, besides that this research also contributes to members of the company's board of commissioners to pay attention to managers in managing company efficiency in choosing CEOs.